Development Of Ketang-Ketang (Scatophagus Argus) Fish Farming In An Effort To Optimize Estuary Waters For Perepat Permai Fish Farmers Group, Air Jukung Village, Belinyu District, Bangka Regency - Eva Utami; Rendy Rendy; Mohammad Agung Nugraha (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
The potential of estuary waters in mangrove forests in Belinyu, Bangka Regency is quite high. The high potential of these waters is utilized by fish farmers to cultivate brackish water fish. The Perepat Permai fish farmer group in Air Jukung Village, Belinyu Subdistrict, Bangka Regency is a fish farmer who is pioneering the cultivation of ketang-ketang fish. Ketang-ketang fish is characterized by softer, tastier meat and no smell of mud. However, fish farming is still constrained by the problem of low optimization in utilizing production capacity which has an impact on the low quantity and quality of yields. The purpose of this activity is to provide science and technology applications in the form of systems and technology to produce ketang-ketang fish that has a high selling price by optimizing the production capacity of fish farmers. This activity was carried out in fish farming ponds owned by fish farmers in Air Jukung Village, Belinyu District, Bangka Regency. The method of this activity is to carry out cultivation activities by inserting the application of stocking technology and artificial feeding systems in the Belinyu ketang-ketang fish cultivation process. The results of this activity are ketang-ketang fish reared from juvenile size with a length of 7-10 cm growing optimally in ponds. Ponds where ketang-ketang fish are kept in environmental conditions that are suitable for the survival and growth of ketang-ketang fish. The number of ketang-ketang fish meets the fish production capacity. Ketang-ketang fish can be harvested partially within 4-5 months with a length of 20-24 cm and a weight of 200-300 grams per head which is the size of consumption according to market demand.